Responses of Tomatoes Grafting Using Variation of Rootstock against Virus Infection and Tomato Yields - Tri Retno Widyastuti; Sri Sulandari; Sedyo Hartono; Triwidodo Arwiyanto (Jurnal Perlindungan Tanaman Indonesia, 2020)
Grafting methods on tomato have been done to reduce the infection rate of various pathogens. Begomovirus and Crinivirus are important viruses in tomato plants. The research aimed to determine the resistance response of tomato plants to viral infection, and tomato production. Field research was conducted in Harjobinangun, Pakem, Sleman, Yogyakarta in the endemic area of the viral diseases transmitted by Bemisia tabaci. This experiment used a Completely Randomized Design non-factorial with “Servo” as scion and “Amelia”, “H-7996”, “Mawar” as rootstock. The disease development, presence of viral diseases, and tomato yields were observed. PCR detection using Krusty & Hommr primer successfully amplified Begomovirus DNA bands with an approximate size of 580 bp in tomato plant with interveinal chlorosis, curling, thick, rigid, and stunt symptoms. Chlorotic spots and yellowing symptoms successfully amplified using ToCV-CF/ToCV-CR specific primer for the amplification of Tomato chlorosis virus with DNA band approximately size of 360 bp, whereas using TICV-CF/TICV-CR specific primer could not amplify the virus cDNA. The leaves roll upward with purple interveinal symptoms that were not infected by both viruses. Both viral infections affected the quality of the fruit which indicated by a higher number of abnormal fruits. “Servo” grafted onto “Amelia” and non-grafted Servo were tolerant to viral infection, “Servo” grafted onto “H-7996” or to “Mawar variety were susceptible to viral infection, self-grafted Servo were very susceptible to viral infection.